Balancing Career and Life: a Study with Special Reference to Women Employees in Kerala - Mariya T Cheeran; Renjith T A and George Joseph
Work life balance is a broad concept which is closely related and derived from the research of Job satisfaction as explained and researched by Farnaz Namin-Hedayati PhD from Innovent Consulting a boutique consulting and work-life solutions firm in Orlando, Florida Today's workers have many competing responsibilities such as work, children, housework, volunteering, spouse and elderly parent care and this places stress on individuals, families and the communities in which they reside. Work-life conflict is a serious problem that impacts workers, their employers and communities. This paper examines the work life balance of women employees working in Cochin in Kerala